Metabolic Response by 18F-FDG PET/CT in Metastatic Malignant Struma Ovarii Treated With Targeted Therapies. (January 2021) - Seban, Romain-David; Bozec, Laurence; Nascimento-Leite, Camila; Champion, Laurence
Abstract : Abstract: Malignant struma ovarii (MSO) is a rare malignant ovarian tumor, histologically identical to differentiated thyroid cancers. Given the rarity of this disease, there are no treatment guidelines, and the place of imaging for response assessment remains controversial. We report a metabolic response assessed by 18 F-FDG PET/CT in a 71-year-old woman with radioiodine-refractory metastatic MSO treated by targeted therapies (first line with lenvatinib and second line with pazopanib). This case of exceptional response also highlights the usefulness of 18 F-FDG PET/CT for therapeutic assessment of targeted drugs in such a rare clinical entity of malignant MSO.